1982
DOI: 10.1093/nar/10.23.7677
|View full text |Cite
|
Sign up to set email alerts
|

Sea urchin small nuclear RNA genes are organized in distinct tandemhy repeating units

Abstract: The genes coding for the two major small nuclear RNAs in the sea urchin are organized in independent tandem repeating units. The small nuclear RNAs, N1 and N2 were purified from gastrula embryos of Lytechinus variegatus. These RNAs are analogous to the U series of RNA in mammalian cells as judged by their identical 5' termini and the sequence homology of the N1 urchin RNA and U1 mouse RNA. These RNAs were polyadenylated with E. Coli adenylate transferase. A 32PO4 labeled copy of each RNA was made with RNA-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

1983
1983
1995
1995

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…RNA was analyzed by electrophoresis on 10% polyacrylamide gels in 7 M urea as previously described (8). The RNA was detected by autoradiography.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA was analyzed by electrophoresis on 10% polyacrylamide gels in 7 M urea as previously described (8). The RNA was detected by autoradiography.…”
Section: Methodsmentioning
confidence: 99%
“…Sea urchin Ul RNA is encoded by a 1,400-base tandemly repeated gene set (8) and is synthesized at a high rate early in sea urchin development (30). Using isolated nuclei from sea urchin blastula embryos, we report that the Ul RNA is synthesized accurately in vitro.…”
mentioning
confidence: 96%
“…There are dramatic changes in the rates of expression of the small nuclearRNA genes as well (16). We have previously reported that most of the genes coding for Ul RNA are present in a 1.4kb tandemly repeated unit in the sea urchin L. variegatus (17). One copy of the Ul gene is present in each repeating unit.…”
Section: Introductionmentioning
confidence: 99%
“…Strong mU2 expression also rules out promoter occlusion and/or transcriptional interference between closely spaced U2 snRNA genes. In fact, the U2 snRNA genes of Xenopus laevis are organized as 500 to 1,000 tandem repeats of an 831-bp unit (29), which is essentially identical in size to the mU2 repeat unit, and the sea urchin U2 genes are organized as Ϸ25 tandem repeats of a 1.1-kb unit (7).…”
mentioning
confidence: 99%